INDIVIDUAL COUNSELING WITH A CLIENT CENTER APPROACH TO ACADEMIC PROCRASTINATION - Syahrial, Melva; Karneli, Yeni (Program Studi Bimbingan dan Konseling FKIP UNJA, 2024)
This research is based on phenomena that occur in the field which show symptoms of prograstination in students. The aim of this research is to find out what is behind procrastination behavior. This research used a case study approach with the subject studied being one student with symptoms of prograstination. The data collection methods used were interviews, observation and documentation. Meanwhile, data analysis uses content analysis and comparative analysis techniques. The results of the study showed that factors contributed to the client's procrastination behavior. First, clients experience frustration due to low learning outcomes, which then triggers negative emotions and interferes with focus in completing tasks. Second, the client develops a habit of avoiding tasks, even though he is aware that the task is important and must be completed immediately. Third, the client's academic procrastination behavior is relatively high, with consistent delays in starting and completing assignments. Lastly, the gap between plans and time indicates that the client does not have good time management skills, resulting in a lot of time being wasted. Overall, negative emotional factors, task avoidance, inability to manage time, and difficulty starting tasks are the main background for procrastination experienced by clients.